Extracellular Vesicles From Stored Red Blood Cells Convey Heme and Induce Spic Expression on Human Monocytes - Amorim, Carolinne Souza; Moraes, João Alfredo; Magdalena, Ingrid de Jesus; López, Sheila Gutiérrez; Carneiro, Ana Carolina Dudenhoeffer; Nunes, Isabelle Karine da Costa; Pizzatti, Luciana; Sardela, Vinícius Figueiredo; Aquino Neto, Francisco Radler; Mirotti, Luciana Cristina; Pereira, Henrique Marcelo Gualberto; Renovato-Martins, Mariana (Frontiers in Immunology, 2022)
During cold storage, red blood cells (RBC) undergo irreversible morphological changes, hemolysis, and extracellular vesicles (EVs) release. It is known that reinfused stored RBC triggers immune reactions within T-lymphocytes and increases pro-oxidative and immunomodulatory metabolites in the plasma of healthy individuals. Monocytes/macrophages are the primary cells in charge of both uptake of excess heme and recognition of such EVs; however, the effect of reinfusion of stored RBC has not been investigated upon monocytes. Hence, the purpose of this study was to characterize how EVs released by cold-stored RBC impact monocytes. For this, we adopted an ex vivo protocol to mimic autologous blood transfusion. Colorimetric and metabolomic analyses confirmed that cold-stored RBC released increased heme levels. Transcriptomic analysis demonstrated that cold-stored RBC increased the transcript levels of heme-oxygenase 1 and Spic in monocytes, along with an induction of heme-oxygenase-1, CX3CR1, and CD206- known markers of macrophages M2-phenotype. Finally, we have demonstrated that the EVs released by cold-stored RBC were enriched in heme and conveyed to monocytes, triggering Spic expression and an acute production of reactive oxygen species. Finally, our study demonstrates that hemolysis resulting from autologous blood transfusion modifies gene expression patterns in monocytes towards an M2-like phenotype. Furthermore, we highlight the role of EVs released by cold-stored RBC in this scenario, which may act like a damage-associated molecular pattern inducing Spic in monocytes.